Pneumatosis Intestinalis in Patients on Chemotherapy or Molecular Targeted Therapy: Report of 3 Cases - S, Abbeel; PJ, Cuyle; S, Carton; E, Van Cutsem (Archives of Clinical and Medical Case Reports, 2021)
Pneumatosis intestinalis (PI) is a radiological term to describe the presence of gas in the bowel wall. It can occur as a primary disease or secondary to various other causes ranging from benign conditions to life-threatening diseases. We present three cases of PI in patients being treated for different types of gastrointestinal cancer. The diagnosis was made incidentally on follow-up CT scanning for two patients, who had only mild gastrointestinal symptoms. For the last patient, it was diagnosed in the setting of fever and clostridium difficile infection. A conservative treatment was advocated and follow-up imaging showed resolution of the PI in two out of three cases. It is important to distinguish between chemotherapy induced PI and other life-threatening causes of PI, which often require urgent surgery. After resolution, risks and possible benefits of restarting of the culprit agent should be outweighed.